Designing theoretical assessments at nursing higher education institutions: A scoping review - Donough, G.; Daniels, F.M.; Mthimunye, K.D.T. (South African Journal of Higher Education, 2022)
Assessment in higher education remains one of the most reliable forms of assessing the effectiveness of the learning and teaching (L&T) process. Excellence in theory assessment design is, therefore, a pivotal element of the success of many Higher Education Institutions (HEIs) around the world. This scoping review aimed to establish current assessment best practices in nursing at HEIs. The five steps of Arksey and O’Malley’s framework guided this scoping review. Following a systematic search of various databases, including Academic Search Complete, CINAHL, ERIC, MEDLINE, PubMed, Sage Online Journals, SCOPUS, and Wiley Online Library for the period from 2010 to 2020, a rigorous screening process was undertaken by three independent reviewers. The search terms included assessment best practice and nursing education institution. Of the 652 articles screened, 12 studies met the inclusion criteria. Four quantitative, four qualitative, one mixed-method, and three studies that did not specify their design were included. The findings revealed that various factors influence how educators design assessments. Theoretical assessment design is a vital activity and requires collaboration between policymakers and HEIs to enhance the quality designing of assessments by educators through professional development.